2014
DOI: 10.1002/vnl.21451
|View full text |Cite
|
Sign up to set email alerts
|

Effect of modified single‐wall carbon nanotubes on mechanical and morphological properties of thermoplastic elastomer nanocomposites based on (polyamide 6)/(acrylonitrile butadiene rubber)

Abstract: Thermoplastic elastomer nanocomposites based on acrylonitrile butadiene rubber (NBR) and polyamide 6 (PA6), with acid functionalized single-wall carbon nanotubes (SWNT), were prepared via a direct melt-mixing process in an internal mixer. The influence of SWNT content (0, 0.5, 1, 1.5) on morphological properties of PA6/ NBR with different ratios (80/20, 70/30, 60/40) were then investigated. Characterization of nanocomposites was conducted by using transmission electron microscopy, scanning electron microscopy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…These high performance rubbers exhibit excellent abrasion/ adhesion resistance and superior mechanical properties for their wide range of applications. NBR is not crystallizable under high strain, and therefore the reinforcing fillers are generally incorporated to yield sufficiently high mechanical properties [ 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 192 , 193 , 194 , 195 , 196 ]. Chougule and Giese [ 93 ] reported significant mechanical reinforcing effects of CNT as compared with CB in NBR due to good dispersion and effective interaction.…”
Section: Mechanical Properties Of Rubber Nanocomposites Of Carbon mentioning
confidence: 99%
See 1 more Smart Citation
“…These high performance rubbers exhibit excellent abrasion/ adhesion resistance and superior mechanical properties for their wide range of applications. NBR is not crystallizable under high strain, and therefore the reinforcing fillers are generally incorporated to yield sufficiently high mechanical properties [ 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 192 , 193 , 194 , 195 , 196 ]. Chougule and Giese [ 93 ] reported significant mechanical reinforcing effects of CNT as compared with CB in NBR due to good dispersion and effective interaction.…”
Section: Mechanical Properties Of Rubber Nanocomposites Of Carbon mentioning
confidence: 99%
“…Desai et al [ 109 ] observed co-continuous phase in TPU:NBR (50:50) blend, owing to uniformly dispersed phases. However, there exists limited work only on the carbon based hybrid fillers reinforced Polyamide 6/NBR/SWCNT [ 91 ]. NBR/PVC/SWCNT, [ 92 ] TPPU/XNBR/MWCNT, [ 110 ] EPDM/NBR/MWCNT [ 111 ], and hybrid filled TPU/NBR blend nanocomposites [ 112 , 113 , 114 ] MWCNTs filled thermoplastic polyurethane-urea (TPUU) and carboxylated acrylonitrile butadiene rubber (XNBR) blend nanocomposites exhibited increased tensile modulus from about 9.90 to 45.3 MPa, at 3 wt % loading of CNT [ 110 ].…”
Section: Mechanical Properties Of Rubber Nanocomposites Of Carbon mentioning
confidence: 99%
“…Samples with various formulations (according to Table 2) was mixed at 240 C and 80 rpm for 7 min. 5,24 After melt-mixing the materials, they were dried for about 12 h at 80 C in an oven. The suitable samples for tests with the relevant standard size were molded by the hot press (Collin P 200 E-type) at 250 C for 6 min.…”
Section: Preparation Of the Nanocompositesmentioning
confidence: 99%
“…However, there exists limited work only on the carbon based hybrid fillers reinforced Polyamide 6/NBR/SWCNT. [91] NBR/PVC/SWCNT, [92] TPPU/XNBR/MWCNT, [110] EPDM/NBR/MWCNT [111] and hybrid filled TPU/NBR blend nanocomposites [112][113][114] MWCNTs filled thermoplastic polyurethane-urea (TPUU) and carboxylated acrylonitrile butadiene rubber (XNBR) blend nanocomposites exhibited increased tensile modulus from about 9.90 to 45.3 MPa, at 3 wt% loading of CNT [110]. Hoikkanen et al, [111] Shang et al, [118] fabricated series of high temperature vulcanized silicone rubber (HTVSR)/MWCNTs nanocomposites with different CNT contents.…”
Section: Mechanical Properties Of Carbon Filler Incorporated Nbr and mentioning
confidence: 99%